Longitudinal shock of two elastic bars with the 2nd bar bases on rigid foundation and meets visco-elastic resistance on side face - An, Nguyen Thuc; To, Nguyen Dang; Son, Nguyen Hung (Vietnam Journal of Mechanics, 1996)
In this paper authors have studied problem of longitudinal shock of two elastic bars with more general model [1, 2]. Technically the model of this problem similar to driving pile, where the pile bases on rigid foundation and meets visco-elastic resistance of foundation on side face of the pile.